Communication in Digital-Based Public Services in Regional Government of West Java Province - Udaya Madjid; Megandaru Widhi Kawuryan; Ahmad Averus; Triyanto Triyanto (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
In digital era, all activities including services to the community certainly use digital media. In addition, the use of digital media is currently the main backbone of communication and change in the economic, social, cultural, and political fields. Therefore, this study aimed to analyze the application of digital-based government communication in public services in West Java Provincial Government, specifically regional government websites and social media, such as Facebook and Twitter. This was based on the dimensions of Content, Services, and Technical Qualities. A qualitative descriptive method was used, and the data analysis was conducted through documentation, observation, in-depth interviews, and social network analysis. The results showed that public services with information and communication technology have been adequately implemented in all West Java Provincial Government agencies. However, there were still several factors that need to be improved, including the discovery of website channels that could not be accessed even though the website is very important in providing official information and communication. In general, the menus that function as information providers were still one-way and have not provided public access to interactive services. Keywords: government communication; digital; public services